Nuclear position and local acetyl-CoA production regulate chromatin state - Willnow, Philipp; Teleman, Aurelio A. (Nature, 2024)
Histone acetylation regulates gene expression, cell function and cell fate1. Here we study the pattern of histone acetylation in the epithelial tissue of the Drosophila wing disc. H3K18ac, H4K8ac and total lysine acetylation are increased in the outer rim of the disc. This acetylation pattern is controlled by nuclear position, whereby nuclei continuously move from apical to basal locations within the epithelium and exhibit high levels of H3K18ac when they are in proximity to the tissue surface. These surface nuclei have increased levels of acetyl-CoA synthase, which generates the acetyl-CoA for histone acetylation. The carbon source for histone acetylation in the rim is fatty acid β-oxidation, which is also increased in the rim. Inhibition of fatty acid β-oxidation causes H3K18ac levels to decrease in the genomic proximity of genes involved in disc development. In summary, there is a physical mark of the outer rim of the wing and other imaginal epithelia in Drosophila that affects gene expression.
Gesehen am 16.12.2024